Native language interference in learning english as a foreign language: an analysis of written material produced by spanish speaking students in senior high school classes - Maldonado Caicedo, María Cristina (2010)
Talking about language as an exclusive art of the human beings means to embrace an exciting topic in which brain functions are related. They determine the cognitive and moving development of learning; the cultural environment which is responsible of the mother tongue that is taught by imitation and subsequently ruled by the educational institutions. When combining the cognitive development with the cultural environment of individuals, the development of a native language is obtained. Therefore, it will be used as a communicative tool in a written and oral way.